L’influence des usages numériques des étudiants sur la réussite universitaire - Christophe Michaut; Marine Roche (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Many studies describe digital uses and practices of students without estimating the effects they produce on learning processes and academic success at a university level. This article explores how digital technology impacts the ways people study and how well they do in their exams. It is based on a quantitative survey of 625 French students registered in undergraduate university in different fields: Health, Sciences and Technology, as well as Literature, Humanities and Social Sciences. First of all, the survey seeks to measure the intensity of academic digital activities: downloading (or not) of files put online by teachers; interactions at a distance between students; taking notes with a computer or a pen; time spent studying on the Internet, etc. Furthermore, it tries to determine the level of influence of the digital activities on the average grades during the first semester. The effects of determining factors – educational background and learning strategies – were controlled. Analyses indicate that students make little use of digital tools to study and when they use them, it is mainly in an instrumental way. Besides, statistical models reveal absence of significant effect of digital activities of the students on exam results.